Unveiling the Benefits of Hajj Funds Investment in Indonesia - Hulwati Hulwati; Slamet Mujiono; Roni Andespa; Abdi Fadhlan (Share: Jurnal Ekonomi dan Keuangan Islam, 2023)
This article aims to investigate the benefits of investing in Hajj funds deposited by waitlisted pilgrims, not only for the purpose of organizing the pilgrimage but also for the wider community in Indonesia. The study draws upon primary data obtained from interviews conducted with the Public Relations of the Hajj Financial Management Agency (BPKH) and the Director of Hajj and Umrah Management of the Ministry of Religious Affairs in Jakarta. Additionally, secondary data was obtained from a variety of sources such as books, online news articles, and reports published by the BPKH that address the value of investment benefits for the Hajj pilgrimage. The selection of the BPKH is based on its responsibility for managing and investing in Hajj funds under Law Number 34 of 2014. The study highlights that Hajj funds investment not only benefits the management of Hajj operations but also has value for the wider community. The findings of this study supplement previous research that has focused primarily on the management of Hajj investments and their juridical basis in Indonesia. The benefit value of Hajj funds is optimally utilized for the implementation of the pilgrimage, as well as for the benefit of the ummah. Such benefits include the provision of religious, educational, and social facilities, as well as disaster relief such as the COVID-19 pandemic. The study concludes that in order to maximize the benefits of Hajj funds investments, they must be directed towards more productive investment opportunities that yield maximum return.====================================================================================================ABSTRAK –  Menyingkap Manfaat Investasi Dana Haji di Indonesia. Artikel ini bertujuan untuk mengeksplorasi nilai manfaat dari investasi dana haji yang disetor oleh calon jamaah haji yang masih dalam daftar tunggu, tidak hanya untuk tujuan penyelenggaraan ibadah haji tetapi juga untuk masyarakat Indonesia secara umum. Data primer untuk penelitian ini diperoleh melalui wawancara dengan Humas Badan Pengelola Keuangan Haji (BPKH) dan Direktur Penyelenggaraan Haji dan Umrah Kementerian Agama di Jakarta. Sementara data sekunder diperoleh dari buku, artikel, berita online, dan laporan-laporan yang diterbitkan oleh BPKH yang membahas tentang nilai manfaat investasi dana haji. Pemilihan BPKH sebagai sumber data didasarkan pada tanggung jawabnya dalam pengelolaan dan investasi dana haji sesuai dengan Undang-Undang Nomor 34 Tahun 2014. Hasil kajian ini menunjukkan bahwa investasi dana haji tidak hanya memberikan nilai manfaat bagi penyelenggaraan operasional haji tetapi juga memberikan nilai manfaat bagi kemaslahatan umat. Temuan ini mendukung beberapa penelitian sebelumnya tentang pengelolaan dana haji dan basis yuridisnya di Indonesia. Nilai manfaat dari dana haji dapat dioptimalkan untuk penyelenggaraan ibadah haji dan kemaslahatan umat, seperti penyediaan fasilitas keagamaan, pendidikan, dan sosial, serta bantuan dalam bencana seperti pandemi COVID-19. Penelitian ini menyimpulkan bahwa untuk memaksimalkan nilai manfaat dana haji, investasinya harus diarahkan pada peluang yang lebih produktif dan menghasilkan keuntungan maksimal.